Metabolic Engineering of Microorganisms as the Current Paradigm of Biopharmaceutical Discovery, Development and Production: Contributions of Synthetic Biology - Gül, Esra; Çelik, Venhar (Dicle Üniversitesi, 2022)
Natural compounds and derivatives play an important role in the pharmaceutical industry. However, difficulties in isolating or chemically resynthesizing these products from the natural host often limit their availability, increase costs, and slow down the biopharmaceutical production process. Pharmaceutical metabolic engineering plays an important role in the discovery, design and manufacture of drugs as well as drug precursors. Because of the ease with which microorganisms are grown at higher titers and less costly, the stable production of small molecule drugs heterologously in a microbial host at high speed, low cost, and high yield is becoming an increasingly popular alternative to their production or chemical synthesis in natural hosts such as plants. Metabolic engineering allows the development of new microbial cell factories and refinement of existing industrial organisms by examining the physiological consequences of certain genetic differences in microorganisms, plants and animals, as well as designing mathematical and computational methods to understand the links between genes and cell functions. It uses synthetic biology methodologies to design, construct and optimize new synthetic pathways by integrating various heterologous biosynthetic pathways with endogenous metabolic pathways in microorganisms. Optimizing metabolically engineered organisms requires a good understanding of the production of these endogenic and heterologous pathway proteins at balanced levels. Thus, the application of metabolic engineering can enable the efficient production of large quantities of biopharmaceuticals in heterologous microorganisms aimed at speeding up the entire production process. In this review study, the design, production and optimization conditions of the production of biopharmaceuticals in microbial cell factories with the metabolic engineering approach were examined.

Farmasötik endüstrisinde doğal bileşikler ve türevler önemli bir rol oynar. Ancak bu ürünlerin doğal konaktan izole edilmesindeki veya yeniden kimyasal olarak sentezlenmesindeki zorluklar, genellikle bunların bulunabilirliğini sınırlar, maliyeti yükseltir ve biyofarmasötik üretim sürecini yavaşlatır. Farmasötik metabolik mühendisliği, ilaçların ve ayrıca ilaç öncüllerinin keşif, tasarım ve üretiminde önemli bir rol oynamaktadır. Mikroorganizmaların daha yüksek titreler ve daha az maliyetle büyütülme kolaylığı nedeniyle küçük moleküllü ilaçların heterolog olarak bir mikrobiyal konakta yüksek hızda, düşük maliyet ve yüksek verimle istikrarlı olarak üretilmesi, bitkiler gibi doğal konaklarda üretimine veya kimyasal sentezine göre giderek daha popüler bir alternatif haline gelmektedir. Metabolik mühendisliği, mikroorganizmalar, bitkiler ve hayvanlardaki belirli genetik farklılıkların fizyolojik sonuçlarını inceleyerek ve ayrıca genler ve hücre fonksiyonları arasındaki bağlantıları anlamak için matematiksel ve hesaplamalı yöntemler tasarlayarak yeni mikrobiyal hücre fabrikalarının geliştirilmesine ve mevcut endüstriyel organizmaların iyileştirilmesine olanak tanır. Mikroorganizmalardaki endojenik metabolik yolaklarla çeşitli heterolog biyosentetik yolakların entegre edilerek yeni sentetik yolakların tasarlanması, inşası ve optimizasyonu için sentetik biyoloji metodolojilerini kullanır. Metabolik olarak tasarlanmış organizmaların optimizasyonu, bu endojenik ve heterolog yolak proteinlerinin dengeli düzeylerde üretilmesinin iyi anlaşılmasını gerektirir. Böylece, metabolik mühendisliğinin uygulanması, tüm üretim sürecini hızlandırmayı amaçlayan heterolog mikroorganizmalarda büyük miktarlarda biyofarmasötiklerin verimli bir şekilde üretilmesini sağlayabilir. Bu derleme çalışmasında biyofarmasötiklerin metabolik mühendisliği yaklaşımıyla mikrobiyal hücre fabrikalarında üretiminin tasarlanması, üretimi ve optimizasyon koşulları incelenmiştir.
Biyofarmasötik Keşif, Geliştirme ve Üretimin Güncel Paradigması Olarak Mikroorganizmaların Metabolik Mühendisliği: Sentetik Biyolojinin Katkıları
Keywords: Structural Biology; Yapısal Biyoloji